2013
DOI: 10.1177/0961203313512883
|View full text |Cite
|
Sign up to set email alerts
|

The American College of Rheumatology and the Systemic Lupus International Collaborating Clinics Classification criteria for systemic lupus erythematosus in two multiethnic cohorts: a commentary

Abstract: The authors offer some comments on the advantages and possible drawbacks of using the SLICC criteria in longitudinal observational studies and clinical trials after applying and comparing them to the ACR criteria in two multinational, multiethnic lupus cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 15 publications
2
55
1
7
Order By: Relevance
“…Possibly the most controversial change brought by the SLICC 2012 is ending the "double counting" of photosensitive malar rash as 2 criteria, as allowed with the ACR 1997 (10,11). In fact, we found this to be the most frequent cause for losing SLE classification by the SLICC 2012 when achieved by the ACR 1997.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Possibly the most controversial change brought by the SLICC 2012 is ending the "double counting" of photosensitive malar rash as 2 criteria, as allowed with the ACR 1997 (10,11). In fact, we found this to be the most frequent cause for losing SLE classification by the SLICC 2012 when achieved by the ACR 1997.…”
Section: Discussionmentioning
confidence: 79%
“…On the contrary, a study in the LUMINA and Grupo Latino Americano de Estudio del Lupus Eritematoso (GLADEL) cohorts showed that the proportion of patients fulfilling the ACR 1997 earlier in the disease course was larger than for the SLICC 2012. However, as noted, this study had no data on several clinical and immunologic manifestations newly included in SLICC 2012 (11).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A large proportion of SCLE (up to 50%) do not fulfill the American College of Rheumatology criteria [2,4,5]. These are the pitfalls associated with the diagnosis of connective tissue diseases which have protean manifestation [6]. This patient presented with an assemblage of cutaneous signs and arthritis without severe systemic involvement.…”
Section: Discussionmentioning
confidence: 99%